1994
DOI: 10.1002/pen.760341706
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of injection molded liquid crystalline polymer/amorphous polymer blends

Abstract: Injection molded samples of binary blends of Vectra (LCP) and the three amorphous polymers polyethersulfone (PES), polycarbonate (PC), and aromatic poly(ester carbonate) (APEC) have been subjected to morphological and rheological characterization, and coefficients of linear thermal expansion and Young's moduli have been determined. The Young's modulus of the PES/LCP blends exhibited a near lower‐bound behavior that could be predicted by the one‐adjustable‐parameter equations of Halpin‐Tsai (ζ = 0.18) and Takay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 32 publications
5
40
0
Order By: Relevance
“…Other articles on PES/LCP blends studied the transport properties of methanol in the blends 25 and measured the interfacial tension by different methods. 12,26 Both extruded 9,18,19,21,22,24 and injectionmolded [13][14][15]22 PES-based blends were studied. The rest of the blends were processed by other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Other articles on PES/LCP blends studied the transport properties of methanol in the blends 25 and measured the interfacial tension by different methods. 12,26 Both extruded 9,18,19,21,22,24 and injectionmolded [13][14][15]22 PES-based blends were studied. The rest of the blends were processed by other methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, the upper part of the curve becomes higher with the increase of LCP weight fraction. The variability of Tg for immiscible LCP/PC blends has been the subject of other studies [25][26][27][28]. So far, the reason for the increase of Tg is not fully understood.…”
Section: Determination Of Phase Transition Temperaturesmentioning
confidence: 98%
“…So far, the reason for the increase of Tg is not fully understood. It has been suggested that transesterification is one of the factors [25,28]. However, the variation of free volume behavior during thermally induced phase separation could be the major cause of the fluctuating Tg of the PC-rich phase [25].…”
Section: Determination Of Phase Transition Temperaturesmentioning
confidence: 99%
See 2 more Smart Citations